Comparative Study of the Legal Maxims Raf‘u al-Haraj and Daf‘u al-Dharar in Relation to the Fundamental Principles of Western Law - Yusrawati Yusrawati (Talenta Publisher, 2026)
The research is grounded in the premise that both legal traditions seek to achieve justice and protect human welfare, yet they operate within distinct philosophical and normative frameworks. The objective of this research is to analyze the conceptual foundations of these Islamic legal maxims, identify corresponding principles in Western law, and systematically evaluate their similarities and differences from both philosophical and juridical perspectives. The study employs a normative juridical research design with a comparative law approach. The methods used include statute, conceptual, and comparative approaches, supported by library-based data collection involving primary, secondary, and tertiary legal materials. Data are analyzed qualitatively through legal interpretation, doctrinal analysis, and comparative evaluation to generate structured and coherent findings. The findings indicate that both raf‘u al-haraj and daf‘u al-dharar share functional similarities with Western legal principles such as proportionality, equity, and harm prevention, particularly in their role of mitigating hardship and preventing injustice. However, fundamental differences arise in their epistemological bases, where Islamic law is rooted in divine revelation and maqāṣid-oriented reasoning, while Western law is grounded in secular rationality and institutional legal structures. The novelty of this research lies in its integrated comparative framework that not only highlights conceptual convergence but also critically delineates structural and philosophical distinctions, thereby contributing to the development of a more comprehensive and responsive legal discourse in a global context